Liquid Biopsy for Colorectal Cancer: Advancing Detection and Clinical Application - Yan Li; Qiong Zhang; Shelly Cook (International Journal of Translational Medicine)
Colorectal cancer (CRC) is the third most common cancer and a leading cause of cancer-related mortality worldwide, with prognosis significantly deteriorating at advanced stages. While current diagnostic methods, such as colonoscopy and tissue biopsy, are widely employed in clinical practice, they are invasive, expensive, and limited in assessing tumor heterogeneity and monitoring disease processes, including therapy response. Therefore, early and accurate detection, coupled with minimal invasion and cost-effective strategies, are critical for improving patient outcomes. Liquid biopsy has emerged as a promising, minimally invasive alternative, enabling the detection of tumor-derived components. This approach is increasingly utilized in clinical settings. The current key liquid biopsy modalities in CRC include circulating tumor DNA (ctDNA), circulating tumor cells (CTCs), and RNA-based biomarkers such as long non-coding RNAs (lncRNAs), microRNAs(miRNAs), and circular RNAs (circRNAs), and tumor-educated platelets (TEPs). These methods provide valuable insights into genetic and epigenetic tumor alterations, and serve as indicators for early detection, treatment monitoring, and recurrence prediction. However, challenges such as assay standardization and variability in sensitivity persist. This review delves into the clinical applications of liquid biopsy in CRC management, highlighting the transformative roles of ctDNA, CTCs, and non-coding RNAs, TEPs in early detection, prognostic assessment, and personalized therapy. In addition, it addresses current limitations and explores potential advancements to facilitate their integration into routine clinical practice.